2018
DOI: 10.1152/physiolgenomics.00124.2017
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling reveals gland-specific differential expression in the three major salivary glands of the adult mouse

Abstract: RNA-Seq was used to better understand the molecular nature of the biological differences among the three major exocrine salivary glands in mammals. Transcriptional profiling found that the adult murine parotid, submandibular, and sublingual salivary glands express greater than 14,300 protein-coding genes, and nearly 2,000 of these genes were differentially expressed. Principle component analysis of the differentially expressed genes revealed three distinct clusters according to gland type. The three salivary g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(79 citation statements)
references
References 52 publications
8
71
0
Order By: Relevance
“…The percentage of SEG s ( FPKM ≥ 0.1 cutoff) was normalized to the total number of expressed protein‐coding genes on a given chromosome (see ref. ). The percentage is given above each bar for the corresponding chromosome.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The percentage of SEG s ( FPKM ≥ 0.1 cutoff) was normalized to the total number of expressed protein‐coding genes on a given chromosome (see ref. ). The percentage is given above each bar for the corresponding chromosome.…”
Section: Resultsmentioning
confidence: 97%
“…RNA sequencing libraries were generated for the PG, SMG, and SLG from three male and three female adult C57BL/6J mice (Jackson Laboratories) as previously described [17]. The data were subjected to analysis using the platform provided by DNAnexus (Mountain View, CA, USA) and then: Gene expression level was expressed as fragments per kilobase of transcript per million of mapped reads (FPKM), which were scaled via the median of the geometric means of fragment counts across all sequencing libraries.…”
Section: Rna Sequence Data and Analysesmentioning
confidence: 99%
“…As such, BPIFA2 may play a protective function to prevent endotoxemia caused by ingested LPS. Interestingly, high levels of BPIFA2 expression have been reported in species that engage in coprophagy, including non-human primates (Thamadilok et al, 2019), dogs (Pasha et al, 2018;Torres et al, 2018), and rodents (Gao et al, 2018;Mirels and Ball, 1992;Venkatesh et al, 2004). Thus, it is possible that expression of this protein has evolved to facilitate nutrient extraction from feces or to protect against ingested LPS.…”
Section: Discussionmentioning
confidence: 99%
“…BPIFA2 (BPI fold containing family A member 2 (Bingle et al, 2011); former names: Parotid Secretory Protein (PSP), SPLUNC2, C20orf70) was first described as a leucine-rich protein in salivary glands (Wallach et al, 1975) and identified as Parotid Secretory Protein in mouse parotid glands (Owerbach and Hjorth, 1980). BPIFA2 is abundantly expressed in all three major mouse salivary glands (Gao et al, 2018) and human salivary glands (Geetha et al, 2003). The protein has been isolated from human saliva (Geetha et al, 2003) where it represents about 5% of total protein (Ruhl, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…3K). Transcriptome analysis to detect SMG secretory genes previously identified from RNA Seq studies (Gao et al 2018) indicated that mRNAs encoding major secretory products were sustained at day 3 and 14 in resected glands (Appendix Fig. 5).…”
Section: Proliferation Is Transiently Upregulated After Partial Glandmentioning
confidence: 94%